PENGARUH MODEL CREATIVE PROBLEM SOLVING (CPS) BERBANTUAN MEDIA MAGIC STRAW TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA KELAS V SEKOLAH DASAR - Pebriyanti, Paola; Rahayu, Puji; Rosmana, Primanita Sholihah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Creative Problem Solving (CPS) learning model assisted by Magic Straw media on the mathematical creative thinking ability of fifth grade students at SDN Sindangsari 04, Bekasi Regency. The research method used was a quantitative study with a Quasi-Experimental Design using two classes, namely class VA as the experimental class and class VB as the control class. The research sample consisted of 24 students in each class with equal backgrounds and levels of ability. The t-test (Independent Sample t-test) was used to test the effect of the Creative Problem Solving learning model assisted by Magic Straw media on students’ mathematical creative thinking ability. The results showed that the significance value (Sig. 2-tailed) was 0.001 < 0.05, which means that there was a significant difference between the two classes. The N-Gain value in the experimental class was 0.68 (medium category), while in the control class it was 0.42 (lower medium category). Thus, it can be concluded that there is a significant effect of the Creative Problem Solving learning model assisted by Magic Straw media on the mathematical creative thinking ability of fifth grade students at SDN Sindangsari 04, Bekasi Regency.